2023
DOI: 10.1007/s00247-023-05793-5
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography imaging phenotypes of hepatoblastoma identified from radiomics signatures are associated with the efficacy of neoadjuvant chemotherapy

Yingqian Chen,
Matthias F. Froelich,
Hishan Tharmaseelan
et al.

Abstract: Background Though neoadjuvant chemotherapy has been widely used in the treatment of hepatoblastoma, there still lacks an effective way to predict its effect. Objective To characterize hepatoblastoma based on radiomics image features and identify radiomics-based lesion phenotypes by unsupervised machine learning, intended to build a classifier to predict the response to neoadjuvant chemotherapy. Materials and methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In HB, the use of texture features improved the specificity and sensitivity of chemotherapy response prediction. A recent study (Chen et al 2024 ) used unsupervised machine learning to cluster HBs based on their heterogeneity. The researchers found that HBs in different clusters differed in terms of clinical features and chemotherapy relevance.…”
Section: Discussionmentioning
confidence: 99%
“…In HB, the use of texture features improved the specificity and sensitivity of chemotherapy response prediction. A recent study (Chen et al 2024 ) used unsupervised machine learning to cluster HBs based on their heterogeneity. The researchers found that HBs in different clusters differed in terms of clinical features and chemotherapy relevance.…”
Section: Discussionmentioning
confidence: 99%